2002
DOI: 10.4269/ajtmh.2002.67.289
|View full text |Cite
|
Sign up to set email alerts
|

Novel primer sequences for polymerase chain reaction-based detection of Trypanosoma brucei gambiense.

Abstract: Abstract. Progress in diagnosis, treatment, and epidemiology of human African trypanosomiasis (sleeping sickness) depends on the existence of specific and sensitive diagnostic tools. Inherent shortcomings of serologic and parasitologic diagnostic methods can be overcome by molecular techniques. Therefore, we have developed a new polymerase chain reaction (PCR) test using primers derived from the recently identified sequence of the Trypanosoma brucei gambiensespecific glycoprotein (TgsGP). The specificity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 54 publications
4
147
1
Order By: Relevance
“…The recently developed T. b. gambiense-specific PCR test based on the use of the T. gambiense-specific glycoprotein gene can also facilitate the correct diagnosis of both parasites that cause sleeping sickness. 22,23 Since the VSG gene sequences of T. brucei show high mutation rates, this can hamper their use in diagnostic and epidemiologic studies. 24 Indeed, the use of the AnTat 11.17 and LiTat 1.3 (CATT antigen) VSG sequences in identifying T. b. gambiense showed that these genes and their products, although present in most strains, may be missing in some isolates from northwestern Uganda and Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed T. b. gambiense-specific PCR test based on the use of the T. gambiense-specific glycoprotein gene can also facilitate the correct diagnosis of both parasites that cause sleeping sickness. 22,23 Since the VSG gene sequences of T. brucei show high mutation rates, this can hamper their use in diagnostic and epidemiologic studies. 24 Indeed, the use of the AnTat 11.17 and LiTat 1.3 (CATT antigen) VSG sequences in identifying T. b. gambiense showed that these genes and their products, although present in most strains, may be missing in some isolates from northwestern Uganda and Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…These are PCR based, targeting the serum resistanceassociated (SRA) gene that is specific for T. b. rhodesiense (4,6,14) or the T. b. gambiense surface glycoprotein (TgSGP) that is specific for that subspecies (2,15). The need for specialized equipment and a constant supply of electricity has hindered integration of those techniques into the diagnostic algorithm.…”
mentioning
confidence: 99%
“…gambiense, respectively; T.b. brucei has neither (3,4). Over 20 species and subspecies of tsetse flies (Glossina spp.)…”
Section: Introductionmentioning
confidence: 99%